The Effect of The Policy of Imposition of Import Duties on The Import of Indonesian Ceramic Tiles - Manullang, Tegdi Subanda; Yudhana Wisnu Gupta, I Made Krisna (Jurnal Indonesia Sosial Sains, 2025)
Indonesia’s current account balance has frequently shown instability, largely influenced by macroeconomic variables such as inflation, exchange rate, and interest rates. This instability has implications for the country’s financial resilience and trade competitiveness. This study aims to analyze the partial and simultaneous effects of inflation, exchange rate, and interest rates on Indonesia’s current account balance using quarterly time series data. The research adopts a quantitative approach utilizing Error Correction Model (ECM) analysis, which allows for the identification of both short-run and long-run relationships among variables. The study finds that inflation and interest rate variables have significant partial effects on the current account, while the exchange rate shows less impact individually. However, when examined simultaneously, all three variables influence the current account significantly. These findings highlight the importance of coordinated macroeconomic policy, especially in managing inflationary pressure and monetary policy responses to safeguard external balance. The results provide valuable insights for policymakers aiming to stabilize Indonesia’s external sector and formulate sustainable economic policies amidst global economic uncertainty.